Impact of a successful intelligence based educational program in the development of analytical skills: Experimental middle school study in Jeddah - Saudi Arabia - - Al-zahrani, Sharefa Ali Mardi (Journal of Educational and Psychological Sciences, 2020)
The aim of the current research is to reveal the effectiveness of an educational program based on the successful intelligence theory of Sternberg in developing the analytical skills of talented students in Jeddah. The research used a descriptive method based on the survey method. The research relied on experimental design with two groups (experimental and control), taking pre and post measurement method. The study adopted the experimental design with two groups (experimental and controlling), taking pre and post measurement method. The study population consisted of all the talented female students in the middle stage in a gifted middle and high school in Jeddah Governorate in the Kingdom of Saudi Arabia, and they numbered (62) students in the academic year (2017/2018). The sample of the study included (42) talented middle school students present in the middle and high school gifted women who were randomly selected and the study sample was divided into two groups, one is experimental (n = 21 students) and the other is control (n = 21). The results indicated that there are statistically significant differences between the mean of the members of the two experimental groups; and they obtained a general average (9.05) in exchange for the control’s obtaining a general average (6.05) in the analytical capabilities scale, while in the post-test of the analytical capabilities, the experimental got a general average of (6,238). In return for the control’s obtaining a general average of (5.524). In light of the results, the researcher recommended the necessity of developing educational programs to develop the analytical capabilities of gifted students in all fields and types, and in various academic courses.